Strategic Securitization: Climate Change in the National Security Narratives of Pakistan - Aman, Ambreen; Hanif, Erum; Choudhary, Ambar (Annals of Human and Social Sciences, 2025)
Strategic securitization represents a deliberate policy approach where states frame environmental risk as a national security threat to achieve diplomatic, economic, and political interests. Climate change has the potential to cause significant uncertain impacts, undermining human security, state survival, and increasing the risks of conflict and instability between states. Climate change is framed as a hard security concern or a strategic opportunity in major powers such as the US, China, and Russia, but Pakistan’s securitization of climate change remains partial, reactive, and development-centric. This qualitative, cross-comparative study analyzes how major powers frame their security priorities, uses discourse analysis and narratives comparison as research methods to identify patterns and differences in strategic narratives, and explores the security implications of climate change and its impacts on the national security of Pakistan. The theoretical framework discusses securitization theory, strategic securitization, and constructivism theory to analyze the changing dynamics of non-traditional security threats. This exploration examines strategic actors and narratives that influence Pakistan’s climate security positioning and contends that securitization of climate change in Pakistan is beginning to emerge through climate diplomacy by using vulnerability as a leverage point for climate finance and justice.